VALIDITY AND RELIABILITY OF ISLAMIC AND INDONESIAN-BASED CONTEXTUAL SCIENCE LITERACY ASSESSMENT INSTRUMENTS - Widiyanti, Fenny; Susilayati, Muslimah (Science Education, Institut Agama Islam Negeri Ponorogo, 2023)
This study aims to determine the validity of the Islamic and Indonesian-based contextual scientific literacy assessment instrument (ALSKII) using the Rasch model. This instrument was developed in the context of Covid-19 as a socio-scientific issue that is presented in a structured manner with a plural model, namely scientific and socio-scientific. The scientific model represents the content of science which is presented in three models, namely mechanistic, systematic, and mathematical. The socio-scientific model is a scientific context that is integrated with religion and nation. This instrument has five skills which are made into 25 question items. The sample of this research is 75 final-semester science education students who were selected purposively. The results showed that the Islamic and Indonesian-based contextual scientific literacy assessment instrument was valid and reliable with a person measure the value of 0.73, MNSQ person and item close to 0.0, person and ZSTD item close to 1.0, Cronbach alpha 0.67, person reliability 0.64 and item reliability 0.95. This instrument can be an alternative in the assessment of scientific literacy based on religion and the state. The instrument can also be further developed according to the context and socio-scientific issues that need to be solved in the community.